In-N-Out Burger : the perils of political contribution - Muldoon, Maria, (SAGE Business Cases., 2019)
On August 29, 2018 Eric Bauman, Chairman of the Democratic Party of California sent out a midnight tweet exposing In-N-Out Burger's donation of $25,000 to the Republican party and called for a nation-wide boycott. In-N-Out's response to the viral sensation could affect their reputation in their home state of California and alter their corporate political donation policy.